Meningkatkan Keaktifan Siswa Pada Mata Pelajaran PAI Melalui Model Pembelajaran Kooperative Tipe Jigsaw Di Kelas VIII SMPN 10 Kota Serang - Sudrajat, Sanin; Munawaroh, Munawaroh (LPPM Universitas Bina Bangsa, 2024)
This research aims to analyze: First, the level of implementation of the jigsaw type cooperative learning method; student learning activity before and after applying the jigsaw type cooperative method. This research was conducted at SMP N 10 Serang City, specifically in class VIII B. This research used the classroom action research (PTK) method, which is one of the efforts that teachers can make to improve the quality of teachers' roles and responsibilities, especially in managing learning. What focuses on the learning process is known as Classroom Action Research. The sample in this study was 38 students in class VIII B. The research procedures or steps carried out are divided into activity cycles which refer to the Kemmis and Kaggart model, where each cycle consists of planning (Plan), Implementation (Action), Observation (Observation), and Reflection (Reflection), these four activities take place simultaneously and the sequence can be modified. The research instruments used observation sheets, questionnaires, and skills/psychomotor assessment tests